Pelatihan Pembelajaran Berdiferensiasi Berbasis Digital dengan Canva bagi Sekolah Penggerak - Puspita, Desi; Dewi, Nadiya Citra; Putrawansyah, Ferry (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Education units that are part of the driving school program found that the implementation of digital-based differentiated learning, especially using Canva media, is still a challenge. Several aspects that can be seen from the results of observations and interviews include that many teachers in this educational unit are not fully aware of the importance and benefits of digital-based differentiated learning with Canva. The service method chosen to achieve the target of differentiated learning training with Canva starts from Self, Concept Exploration, Collaboration Space, and Demonstration. The work produced by the participants is concrete evidence of the positive impact of this service activity. These works reflect the understanding obtained from the service team regarding the material presented. Participants not only become consumers of information but are also able to turn it into useful work in a learning context